1996
DOI: 10.1074/jbc.271.46.28777
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and Regulation of CTP Synthetase from Saccharomyces cerevisiae by Protein Kinase A

Abstract: The phosphorylation and regulation of the URA7-encoded CTP synthetase (EC 6.3.4.2, UTP:ammonia ligase (ADP-forming)) from Saccharomyces cerevisiae by cAMPdependent protein kinase (protein kinase A) were examined. Protein kinase A is the principal mediator of signals transmitted through the RAS/cAMP pathway in S. cerevisiae. The results of labeling experiments indicated that the phosphorylation of CTP synthetase was mediated by the RAS/cAMP pathway in vivo. In vitro, protein kinase A phosphorylated CTP syntheta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
85
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(94 citation statements)
references
References 39 publications
9
85
0
Order By: Relevance
“…CTP synthetase is phosphorylated by protein kinase A, and it is unknown whether the phosphorylation of CTP synthetase by protein kinase C affects the ability of the enzyme to be phosphorylated by protein kinase A and vice versa. Moreover, data suggest that CTP synthetase is phosphorylated by yet additional protein kinases (34). Thus, the regulation of CTP synthetase by phosphorylation is very complex.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…CTP synthetase is phosphorylated by protein kinase A, and it is unknown whether the phosphorylation of CTP synthetase by protein kinase C affects the ability of the enzyme to be phosphorylated by protein kinase A and vice versa. Moreover, data suggest that CTP synthetase is phosphorylated by yet additional protein kinases (34). Thus, the regulation of CTP synthetase by phosphorylation is very complex.…”
Section: Discussionmentioning
confidence: 97%
“…These phosphorylations result in the stimulation of CTP synthetase activity by a mechanism that increases catalytic turnover (33)(34)(35). In addition, phosphorylation facilitates the nucleotide-dependent tetramerization of the enzyme (29) and causes a decrease in the sensitivity of the enzyme to inhibition by CTP (34,35). Ser 424 has been identified as the target site for protein kinase A phosphorylation (see Fig.…”
Section: ) (30)mentioning
confidence: 99%
“…The phosphorylation of purified URA7-encoded CTP synthetase by protein kinase A and protein kinase C results in the stimulation of enzyme activity by 190 % and 300 %, respectively [74,75]. In vivo labeling studies have shown that the phosphorylation of CTP synthetase by protein kinase A [74] and protein kinase C [75] is physiologically relevant. The stimulation of CTP synthetase by protein kinases A or C may be related to signal transduction pathways that direct the cell growth, proliferation, and biosynthesis of macromolecules.…”
Section: Regulation Of Ctp Synthetase By Phosphorylationmentioning
confidence: 99%
“…The stimulation of CTP synthetase by protein kinases A or C may be related to signal transduction pathways that direct the cell growth, proliferation, and biosynthesis of macromolecules. Kinetic analyses show that the mechanisms for stimulation of CTP synthetase activity by the two different protein kinases are the same [74,75]. Phosphorylated CTP synthetase shows an increase in the V max with respect to the substrates UTP and ATP, a decrease in the K m value toward ATP, and a decrease in the positive cooperativity of the enzyme for ATP [74,75].…”
Section: Regulation Of Ctp Synthetase By Phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation